Role of Primary Stakeholders in Needs Assessment for Local Development Planning - Sapkota, Bhaba Datta (KMC Research Journal, 2023)
The involvement of primary stakeholders in needs assessment becomes not only necessary but strategically imperative. This paper aims to conceptualize the role of primary stakeholders in needs assessment regarding local development planning context. The roles of primary stakeholders in local development planning are subjective and can trace out by interpretative way considering the constructivist standpoint. Methodologically, this paper adopted a descriptive content analysis approach using secondary sources. Prior studies argued different views on the role of primary stakeholders in needs assessment. As a participatory tool, it is remarkable to note that primary stakeholders' involvement in needs assessment, prioritize needs, aid in decision-making, resource allocation, and implementation. Primary stakeholder's involvement in planning and decision-making is challenged by poor communication, ignorance of planning importance, political interference, weak accountability, and bureaucratic dominance. However, the result indicates that the degree of stakeholders' involvement in local development planning and more specifically defining the felt needs within the community is a yardstick and provide a new turning point for further planning and development effort. It helps to reduce the unnecessary cost of the plan and develop proper coordination, collaboration, and consultation in the needs identification process. Stakeholders create a clear road map for sustainable and inclusive planning. Community people are active change agents and can define real development priorities through the assessment process. However, this paper is limited in subjective analysis and only the primary stakeholder's role in needs using limited sources.